(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Similia Similibus Curantur is also called the law of similars. That is, when a drug produces pathological/pathogenic symptoms in healthy individual means, the same drug can relieve similar kinds of symptoms in individuals with the disease. The biological, pharmacological and toxicological action of capsaicin alkaloids is a perfect example to explain the Similia Similibus Curantur principle. Most of the drugs in homoeopathic materia medica contain toxicological, pharmacological, drug-proving, and traditional use-related symptoms and indications. Abnormal sensations and symptoms of the disease are caused by the involvement of a specific receptor or molecular pathway and gene functions. These receptors or molecules may be stimulated or suppressed by environmental, natural or artificial agents. In such conditions, the administration of specific homoeopathic medicine having a similar kind of affinity towards the particular receptors or molecules involved in the disease process leads to modulation of such receptor or molecular pathways (e.g., desensitization, sensitization, inhibition). These kinds of actions cause the betterment of symptoms or curative effects. So “Similia similibus curanter” can be understood as a similar receptor or molecular pathway involved in both drug molecules biological/ pharmacological and toxicological action and disease pathogenesis". The selection of medicine is by comparing the similarity between the receptor or molecular pathway in disease pathogenesis and drug pathogenesis. To avoid unwanted aggravations or side effects while using mother tinctures or solutions, administer them less than their physiological dose. The theory of the pharmacological basis of Similia Similia Curantur creates a rational method to apply this Similia Principle. Based on this theory, there is a possibility of discovering Novel drugs in the future that acts and gives a cure in similia similibus curantur way.